pUL21 regulation of pUs3 kinase activity influences the nature of nuclear envelope deformation by the HSV-2 nuclear egress complex - Muradov, Jamil H.; Finnen, Renée L.; Gulak, Michael A.; Hay, Thomas J. M.; Banfield, Bruce W. (PLoS pathogens, 2021)
It is well established that the herpesvirus nuclear egress complex (NEC) has an intrinsic ability to deform membranes. During viral infection, the membrane-deformation activity of the NEC must be precisely regulated to ensure efficient nuclear egress of capsids. One viral protein known to regulate herpes simplex virus type 2 (HSV-2) NEC activity is the tegument protein pUL21. Cells infected with an HSV-2 mutant lacking pUL21 (ΔUL21) produced a slower migrating species of the viral serine/threonine kinase pUs3 that was shown to be a hyperphosphorylated form of the enzyme. Investigation of the pUs3 substrate profile in ΔUL21-infected cells revealed a prominent band with a molecular weight consistent with that of the NEC components pUL31 and pUL34. Phosphatase sensitivity and retarded mobility in phos-tag SDS-PAGE confirmed that both pUL31 and pUL34 were hyperphosphorylated by pUs3 in the absence of pUL21. To gain insight into the consequences of increased phosphorylation of NEC components, the architecture of the nuclear envelope in cells producing the HSV-2 NEC in the presence or absence of pUs3 was examined. In cells with robust NEC production, invaginations of the inner nuclear membrane were observed that contained budded vesicles of uniform size. By contrast, nuclear envelope deformations protruding outwards from the nucleus, were observed when pUs3 was included in transfections with the HSV-2 NEC. Finally, when pUL21 was included in transfections with the HSV-2 NEC and pUs3, decreased phosphorylation of NEC components was observed in comparison to transfections lacking pUL21. These results demonstrate that pUL21 influences the phosphorylation status of pUs3 and the HSV-2 NEC and that this has consequences for the architecture of the nuclear envelope.